Small African Stock Markets-The Case of the Lusaka Stock Exchange - Marone, Heloisa (IMF Working Papers; Working Paper ;, 2003)
In trend with a global pattern and following recommendations of the World Bank and the International Finance Corporation (IFC), the number of stock markets in African countries has increased dramatically over the last ten years. Despite a scarcity of studies on the impact of stock markets on these economies, some policymakers have been arguing in favor of stock exchanges (national or regional) in eastern and southern Africa. The creation of such exchanges may be a premature project as they might lack an actual economic rationale. The present case study, for instance, suggests that the Lusaka Stock Exchange (LuSE) has little effect on the larger Zambian economy.